Relevance of Kurikulum Merdeka in Islamic Religious Education to Build Independence and Creative in The Muslim Generation - Nadiva, Dewinta (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
The purpose of this study is to examine more deeply the independent learning curriculum inPAI subjects, the relationship between the kurikulum merdeka and character education and itsimplementation in educational institutions. The writing of this scientific article uses the method ofliterature study by using various types of sources both from books and scientific articles from variousjournals, theses, dissertations to find theories and supporting data. The results of this study are that thekurikulum merdeka is very relevant in PAI. This curriculum offers a larger and more holistic approachto teaching Islam and gives young people the opportunity to create their own unique identity based onIslamic principles. The younger generation is also taught critical, independent and creative thinking skillsthrough this curriculum. The future generation of Muslims must be able to think for themselves if theyare to better understand their religion and face difficulties in this dynamic and complex world. In theTechnical Guidance of Strengthening PAI Learning for SMA/SMALB/SMK Based on Blended, it statesthat in kurmer the number of two JP in one week is multiplied by 36 weeks, then 1 JP is added for Islamicreligious projects, resulting in a total of 108 JP each year from the Curriculum and Books Center. As aresult, he argues that the time allotted for the initial and final assessments is meant to gradually improvestudents’ soft skills and character. Because GPAI learning outcomes must conform to standards, schoolsmust learn how to communicate with parents. He also asked teachers to apply various learningapproaches. He believes that an kurikulum merdeka can be created using learning objectives achievementstandards (KKTP), which can include activities that are difficult to interpret.